A twist of nature: a left-handed Bythinella schmidti (Küster, 1852) (Caenogastropoda: Bythinellidae) - Simona Prevorčnik; Andrzej Falniowski (Natura Sloveniae)
As most extant snails, Bythinella schmidti is characterised by dextral (right-handed) coiling of the shell. Nevertheless, a small sinistral (left-handed) individual from the spring on a mountain pasture was sampled, together with its larger dextral conspecifics. In our report on this first case of sinistrality within the superfamily Truncatelloidea, we discuss its shell abnormalities and provide a review on chirality in snails.